2019
DOI: 10.29333/ojcmt/5762
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceptions towards Dairy Products: Effects of Mass Media

Abstract: Using the information from mass media, consumers develop their perceptions towards dairy products. This article examines how these perceptions are developed. Based on a mixed design, our research has three consecutive data collection phases. The first phase is a quantitative content analysis of four major Turkish newspapers, three popular Turkish television health shows and Turkish internet content on dairy products. Second phase is designed to collect qualitative data from three focus groups in order to revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Instead, prior research has either evaluated market segments of fluid milk (Harwood and Drake, 2018) or considered the motivations that might influence consumers to choose plantbased alternatives (McCarthy et al, 2017). Some studies that have compared perceptions of nutrition content in dairy milk and milk alternatives in other countries, such as Australia (Bus and Worsley, 2003a,b), Canada (Préjet, 2018), and Turkey (Atabek and Atabek, 2019), suggest that significant confusion exists in consumer perceptions. In the United States, studies have focused on milk production attributes (Wolf et al, 2011) and consumer segmentation within dairy milk (Bir et al, 2019), finding that consumers are willing to pay significant amounts for aspects including fat content.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, prior research has either evaluated market segments of fluid milk (Harwood and Drake, 2018) or considered the motivations that might influence consumers to choose plantbased alternatives (McCarthy et al, 2017). Some studies that have compared perceptions of nutrition content in dairy milk and milk alternatives in other countries, such as Australia (Bus and Worsley, 2003a,b), Canada (Préjet, 2018), and Turkey (Atabek and Atabek, 2019), suggest that significant confusion exists in consumer perceptions. In the United States, studies have focused on milk production attributes (Wolf et al, 2011) and consumer segmentation within dairy milk (Bir et al, 2019), finding that consumers are willing to pay significant amounts for aspects including fat content.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the perception of the general presence of additives in food and dairy products (Shim et al . 2011; Atabek and Atabek 2019; van der Vossen‐Wijmenga et al . 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Barker et al 2014) reported a significant increase in nutrition and slimmingrelated content through constant exposure to magazines. Yadavalli & Jones (2014), as cited in Atabek & Atabek (2019), demonstrated how media coverage concerning food scare incidents could significantly impact consumer behaviour. Hence, there must be increased media awareness about dairy products' benefits and written in formats and languages that the non-scientific publics will understand.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Hence, Besley et al (2018) call for scientists to inform and communicate with non-scientists about scientific benefits. Atabek & Atabek (2019) add that non-science experts can use the right information for their benefit as research has revealed that consumers develop perceptions (negative, positive, and neutral) and make purchase decisions based on information they have. Science communication is the process of effectively conveying scientific concepts and knowledge to non-scientific audiences.…”
Section: Introductionmentioning
confidence: 99%